2021
DOI: 10.1098/rspb.2020.2513
|View full text |Cite
|
Sign up to set email alerts
|

Rapid behavioural response of urban birds to COVID-19 lockdown

Abstract: Biodiversity is threatened by the growth of urban areas. However, it is still poorly understood how animals can cope with and adapt to these rapid and dramatic transformations of natural environments. The COVID-19 pandemic provides us with a unique opportunity to unveil the mechanisms involved in this process. Lockdown measures imposed in most countries are causing an unprecedented reduction of human activities, giving us an experimental setting to assess the effects of our lifestyle on biodiversity. We studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 74 publications
2
36
0
3
Order By: Relevance
“…Besides, this season is also the breeding period of different resident species sustaining more diversity. In Bangladesh, from March to June movement and general office activities of humans were completely prohibited due to COVID 19, so birds may have more opportunities to move in the urban area (10)(11)(12) . Therefore, it is assumed that species richness and diversity in March and June have increased due to decreased human movement activity.…”
Section: Number Of Individual Of a Species Total Number Of Individuals Of All Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, this season is also the breeding period of different resident species sustaining more diversity. In Bangladesh, from March to June movement and general office activities of humans were completely prohibited due to COVID 19, so birds may have more opportunities to move in the urban area (10)(11)(12) . Therefore, it is assumed that species richness and diversity in March and June have increased due to decreased human movement activity.…”
Section: Number Of Individual Of a Species Total Number Of Individuals Of All Speciesmentioning
confidence: 99%
“…Some studies suggested that urban habitats offer many advantages to wild animals, such as food accessibility, lower predation rate, etc., thus supporting more species relative to other habitats (7)(8)(9)(10) . Situations in urban landscapes like less human disturbance and suitable space for wild animals can gather more species increasing the probability of detection (11) . During the COVID-19 situation, bird diversity and population seems to be increased in the study area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that L. luae is widely distributed across Southeast Asia (Baroga‐Barbecho et al 2020), detectable population differences in the call properties within a small part of its distribution raises further questions on how plasticity and/or microevolution of the calling behaviors may be at play. Population genomic work at the local and regional scales can reveal new insights into their microevolution and behavioral plasticity and how they are impacted by human activities (be it during or after the COVID‐19 crisis), but similar research is hitherto limited to birds (e.g., Gordo et al 2020) and a few cricket species (e.g., Shaw 1996, Lewkiewicz and Zuk 2004).…”
Section: Figmentioning
confidence: 99%
“…Although the effect of urban noise on diurnal bird activity has received attention in the past, a recent study showed that decreases in diurnal bird numbers in noisy urban settings could be related to temporal responses of birds or our inability to detect them in highly noisy conditions (Carral-Murrieta et al, 2020). Also a recently published study from Spain showed a significant increase in bird detectability in the early morning, suggesting a rapid behavioral response of urban birds to novel environmental conditions (Gordo et al, 2021). Nyctibius griseus 3 2 6 3…”
mentioning
confidence: 99%